A three-layered analysis of Turkey's social and economic support program :|intentions, implementations, and gender outcomes - Keleş Yüksel, Şehide Zehra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Female poverty, that can be rendered temporarily invisible by the traditional conjugal union, becomes a non-negligible problem when social aid mechanisms gain essential importance over single-parent households that are in majority led by mothers who themselves have become a new social risk both demographically and politically. Social investment paradigm aims at this new risk in a way to reduce the costs of motherhood and divorce especially for single mothers. This thesis examines a form of gendered economic vulnerability that has become visible with divorce or separation over a welfare program, Socio-economic Support Service (SED). Relying on the interviews with four bureaucrats, eight social workers, and eleven beneficiary single mothers; this study reveals both the challenging and route-making qualities of divergences between the designed, implemented and experienced SED. First it shows that, the criteria that trace whether the beneficiaries really lack alternatives to survive force women to make a choice between men and the state and most women prefer being dependent on the state’s budget. Hence, this policy ends up empowering women who want to build a new life outside the normative family. Secondly, since care policies fail to create alternatives, informal employment and compressed motherhood undermine government’s ideal of warm family environment. Besides, intergenerational transmission of poverty cannot be prevented as long as child poverty is considered separate from gender inequality. Over all, this thesis argues that social policy can give birth to unintended possibilities through practice and interaction of different domains.
Keywords: Support services (Management); Evaluation research (Social action programs)